Variability of Zaleplon 5-Oxidase Activity in Mice and Humans, and Inhibition by Raloxifene - Tanoue, Chiaki; Sugihara, Kazumi; Tayama, Yoshitaka; Uramaru, Naoto; Watanabe, Yoko; Ohta, Shigeru; Kitamura, Shigeyuki (Drug Metabolism Letters, 2016)
Background: Zaleplon (ZAL) is a sedative-hypnotic agent, which is mainly metabolized to inactive 5-oxidized zaleplon (5-oxo-ZAL) and N-des-ethylated ZAL (des-ethyl-ZAL) in mice and humans. The former reaction is considered to be catalyzed by aldehyde oxidase present in liver cytosol. Methods: Here, we examined sex and strain differences of ZAL metabolism to 5-oxo-ZAL among four strains of mice, as well as the inter-individual variation in humans, in order to evaluate the variability of 5-oxo-ZAL-forming activity and its relationship with aldehyde oxidase activity. In mice, the activity in C57BL/6J strain was the highest, followed by C3H/He and BALB/c. The activity in DBA/2J was the lowest, being 2.3-fold lower than that of C57BL/6J mice. The activity of male mice was higher than that of female mice. Large inter-individual variations were observed among humans, with a range of 10- fold. Raloxifene, an inhibitor of aldehyde oxidase, markedly decreased the formation of 5-oxo-ZAL by liver cytosol of mice and humans. Further, the plasma level of 5-oxo-ZAL in mice was decreased when raloxifene was co-administered with ZAL. Results: Our results indicate that the formation of 5-oxo-ZAL from ZAL is mainly catalyzed by aldehyde oxidase in mice and humans, and the variability of 5-oxo-ZAL formation is due primarily to differences of aldehyde oxidase activity. Conclusion: High inter-individual variability of ZAL 5-oxidase activity and potential for interaction of ZAL with other medicines that are inhibitors of aldehyde oxidase should be taken into consideration in clinical usage of ZAL.
Keywords: zaleplon